2023
DOI: 10.1186/s13054-023-04655-8
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of sepsis-associated encephalopathy: a clinical perspective

Romain Sonneville,
Sarah Benghanem,
Lina Jeantin
et al.

Abstract: Sepsis-associated encephalopathy is a severe neurologic syndrome characterized by a diffuse dysfunction of the brain caused by sepsis. This review provides a concise overview of diagnostic tools and management strategies for SAE at the acute phase and in the long term. Early recognition and diagnosis of SAE are crucial for effective management. Because neurologic evaluation can be confounded by several factors in the intensive care unit setting, a multimodal approach is warranted for diagnosis and management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 92 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…Previous studies investigating EEG alterations in sepsis identified that a slower background rhythm in the delta or theta frequencies was observed in 50% of patients and that the absence of reactivity was an independent predictor of mortality ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating EEG alterations in sepsis identified that a slower background rhythm in the delta or theta frequencies was observed in 50% of patients and that the absence of reactivity was an independent predictor of mortality ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is associated with neurologic complications, both in the acute phase and in the long term ( 9 11 ).…”
mentioning
confidence: 99%
“…Sepsis-associated encephalopathy (SAE) is a severe neurological condition linked to sepsis, characterized by altered cognitive function and a range of symptoms from delirium to coma ( Sonneville et al, 2023 ). In a rat sepsis model, sepsis induced blood-brain barrier (BBB) damage and activated ferroptosis in neurons.…”
Section: Exosomal Ferroptosis-related Ncrnas In Pathogenesis Of Human...mentioning
confidence: 99%
“…Cefepime-induced neurotoxicity was defined based on the following one or more symptoms experienced by a patient after cefepime initiation: seizure, altered mental status, myoclonus, agitation and delirium [18]. Creatinine clearance calculation was made by the Cockroft-Gault equation [19].…”
Section: Definitionsmentioning
confidence: 99%